Books known only by title - Lied, Liv Ingeborg (Journal for the study of the pseudepigrapha, 2023)
This special issue of the Journal for the Study of the Pseudepigrapha aims to introduce the concept of “books known only by title” as a fruitful new focus of research in the larger field of first-millennium Jewish and Christian literatures. Books known only by title are named literary objects known only through the medium of other writings, surviving neither as extant documents nor as excerpts or quotations of any substantial length. Still, these books are far more than “lost,” “false,” or “forged”: they were vital components of the first millennium literary imagination. This introductory essay provides a conceptual and methodological framework for the study of this hitherto unexplored phenomenon and offers an initial overview of key functions of books known only by title in book lists and literary texts.